Catalyst-Free Spontaneous Aza-Mannich/Lactamization Cascade Reaction: Easy Access to Polycyclic δ-Lactams - Antonia Di Mola; Caterina Vietri; Consiglia Tedesco; Antonio Massa (Molecules, 2025)
Ring-fused azacyclic compounds are important building blocks in the synthesis of natural products and pharmaceutical agents. Herein, we report an effective and valuable one-pot approach to obtaining polycyclic fused δ-lactams from readily available 2-formylphenyl acetate and diamines under catalyst-free and green conditions.